2021
DOI: 10.1093/cid/ciab510
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Staphylococcus aureus Bacteremia: Clinical Spectrum and Predictors of Poor Outcome

Abstract: Background Staphylococcus aureus is a common cause of bacteremia, yet the epidemiology, and predictors of poor outcome remain inadequately defined in childhood. Methods ISAIAH is a prospective, cross-sectional study of S. aureus bacteremia (SAB), in children hospitalized in Australia and New Zealand, over 24-months (2017–2018). Results Overall, 552 SABs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…21,22,27 A recent large, prospective study evaluating 552 children with S. aureus bacteremia found that whereas developing necrotizing pneumonia increased mortality, the isolation of MRSA did not. 34 Several factors, such as previous MRSA infection or colonization, recurrent skin infections and long-term hemodialysis have been associated with MRSA CAP in adults. 30,38 We found that children with MRSA were more frequently male and more frequently had relevant chronic clinical conditions than those with MSSA.…”
Section: Aguilera-alonso Et Almentioning
confidence: 99%
“…21,22,27 A recent large, prospective study evaluating 552 children with S. aureus bacteremia found that whereas developing necrotizing pneumonia increased mortality, the isolation of MRSA did not. 34 Several factors, such as previous MRSA infection or colonization, recurrent skin infections and long-term hemodialysis have been associated with MRSA CAP in adults. 30,38 We found that children with MRSA were more frequently male and more frequently had relevant chronic clinical conditions than those with MSSA.…”
Section: Aguilera-alonso Et Almentioning
confidence: 99%
“…sepsis, osteomyelitis) and postinfectious complications (i.e. acute rheumatic fever, acute post-streptococcal glomerulonephritis) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“… 26 A recent prospective cross-sectional study by Campbell et al found that 4% of children with SAB had a relapse within 3 months. 31 In that study, IDC was protective against mortality related to SAB (adjusted odds ratio 0.07 with 95% confidence interval [95%CI] 0.004–0.9). 31 In another recent study, Duguid et al retrospectively compared the outcome of pediatric SAB cases with and without IDC.…”
Section: Discussionmentioning
confidence: 86%
“… 31 In that study, IDC was protective against mortality related to SAB (adjusted odds ratio 0.07 with 95% confidence interval [95%CI] 0.004–0.9). 31 In another recent study, Duguid et al retrospectively compared the outcome of pediatric SAB cases with and without IDC. They found that IDC was independently associated with cure, defined as the absence of death or relapse at 30 days (odds ratio 31.5.…”
Section: Discussionmentioning
confidence: 86%